2020
DOI: 10.3390/cells9040919
|View full text |Cite
|
Sign up to set email alerts
|

Signaling of Macrophages that Contours the Tumor Microenvironment for Promoting Cancer Development

Abstract: The immune response is critical in the maintenance of an organism's health. The immune response can be broken down into two groups. The innate response, which is fast-acting and rids the body of most foreign material before infection occurs, and the adaptive response, a more specific defense against pathogen composed mostly of antibody production and killer cells. Linking the two responses via cytokine and chemokine secretion are macrophages, motile phagocytic cells that ingest and present foreign material pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Of the 593 shared DEmRNAs, 577 were upregulated, accounting for 97.3%; thus, we mainly focused on their biological functions. The results indicated that many of them were associated with TME-related processes, such as the immune response, leukocyte migration, antigen binding, and the CAM pathway ( Harjunpaa et al, 2019 ; Cao et al, 2020 ; Messex et al, 2020 ; Sulea et al, 2020 ). Next, ceRNA and PPI networks were constructed.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 593 shared DEmRNAs, 577 were upregulated, accounting for 97.3%; thus, we mainly focused on their biological functions. The results indicated that many of them were associated with TME-related processes, such as the immune response, leukocyte migration, antigen binding, and the CAM pathway ( Harjunpaa et al, 2019 ; Cao et al, 2020 ; Messex et al, 2020 ; Sulea et al, 2020 ). Next, ceRNA and PPI networks were constructed.…”
Section: Discussionmentioning
confidence: 99%
“…A key determinant of host antitumor immunity is the balance of i.t. M1 (tumoricidal) ( 29 ) and M2 (tumorigenic) ( 30 ) macrophages ( 31 ). i.t.…”
Section: Resultsmentioning
confidence: 99%
“…M1 macrophages, stimulated by LPS and interferon gamma, are identified by their production of high levels of pro‐inflammatory cytokines and promotion of the Th1 response in the adaptive immune response. M2 macrophages are activated by IL‐4 or IL‐13 ligands and notably polarized into M2a (anti‐inflammatory, tissue remodelling), M2b (Th2 activation, immunoregulation), M2c (phagocytosis of apoptotic cells), M2d (angiogenesis, tumour progression) subtypes, which are response for tumour progression and the main population of macrophages in TME 43 . IL‐10, IL‐4, IL‐13, CCL2, CCL3, CCL4, CCL5 and MFG‐E8 in TME promote M2 macrophages generation.…”
Section: Composition and Function Of The Tmementioning
confidence: 99%